2015
DOI: 10.5714/cl.2015.16.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of graphene nanoplatelets using sugar azide for graphene/epoxy nanocomposites

Abstract: We report a covalent functionalization of graphene nanoparticles (GnPs) employing 2,3,4-Tri-O-acetyl-β-D-xylopyranosyl azide followed by fabrication of an epoxy/functionalized graphene nanocomposite and an evaluation of its thermo-mechanical performance. Successful functionalization of GnP was confirmed via thermal and spectroscopic study. Raman spectroscopy indicated that the functionalization was on the edge of the graphene sheets; the basal plane was not perturbed as a result of the functionalization. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The diameter of the graphene layers ranges from 1-100 µm, while their thickness is measured in nm [12]. The hydrophobic nanoparticles can be functionalized by covalent (functional groups) and non-covalent (surfactants) modification techniques [13][14][15]. The non-covalent approach depends on polar-polar interactions to prevent solid GNPs from sedimenting into a homogenous slurry by covering the graphene surface area with surfactants/polymers that act as stabilizers [16].…”
Section: Research Motivation and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the graphene layers ranges from 1-100 µm, while their thickness is measured in nm [12]. The hydrophobic nanoparticles can be functionalized by covalent (functional groups) and non-covalent (surfactants) modification techniques [13][14][15]. The non-covalent approach depends on polar-polar interactions to prevent solid GNPs from sedimenting into a homogenous slurry by covering the graphene surface area with surfactants/polymers that act as stabilizers [16].…”
Section: Research Motivation and Literature Reviewmentioning
confidence: 99%
“…Their results showed a 9.22% increment in the thermodynamics properties using 0.1 wt.% nanofluid at a Re of 17,500. Sadri et al [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] produced stable and eco-friendly CGNPs-H 2 O nanofluids for heat transfer and hydrodynamic applications. The friction factor increased by ~3.79% for 0.1 wt.% They believed that the increased pressure drop was due to a minor rise in the viscosity of all of the CGNPs-DW nanofluids, which necessitated a nearly insignificant increase in the fluid velocity due to the constant Re.…”
Section: Research Motivation and Literature Reviewmentioning
confidence: 99%
“…Nano-sized graphite Recently, a large number of papers have reported studies to modify carbon nanoparticles in efforts to improve their dispersibilty in polymer, as well as in solutions, and ultimately to increase targeted properties of polymers [91,92]. The modification of carbon nanoparticles has often focused on chemical modification or functionalization, to covalently attach specific functional groups to their surfaces and edges [93][94][95][96].…”
Section: Dynamic Mechanical and Thermal Properties Of Peti-5/xgnp Commentioning
confidence: 99%
“…Carbon nanoparticle-filled polymer composites have advantages over traditional polymer composites in their mechanical and thermal properties. It has been found that xGnP-filled polymer composites exhibit excellent electrical and thermal conductivities as well as good mechanical properties [4,5] even though they had a low xGnP content of less than 2 vol%. This effect is attributed to the extremely large surface area and the aspect ratio of the xGnP, which leads to the formation of a percolated conducting network within the polymer matrix at concentrations of less than 2 vol% [6,7].…”
Section: Introductionmentioning
confidence: 99%